GOVERNANCE OF ENERGY INTENSITY IMPLEMENTATION: CASE STUDY OF PT ADIRATNA BANI MAKMUR INVESTAMA TBK - Sri Suryaningsum; Nelly Roffiatun; Arika Kusnul Khotimah; Atanindya Naura Lituhayu (CV. Fahr Publishing, 2025)
Climate change and the global energy transition have intensified Indonesia's commitment to energy efficiency, especially in the mining sector, which accounts for 42% of national Greenhouse Gases (GHG) emissions. This study analyzes the implementation of energy intensity governance at PT Adiratna Bani Makmur (ABM) Investama Tbk. (2019-2023) through a quantitative descriptive approach. The results showed significant fluctuations: energy intensity jumped 522.32% (2020) and 69.64% (2022) during the expansion of coal production without technological innovation, but fell by 22.76% (2021) and 57.37% (2023) post-infrastructure investment. Comparatively, PT ABM's performance consistently exceeds the average of the Indonesian mining sector (0.28 SBM/million Rp), with an intensity value of 485.9× the minimum value of the sector (2022). Internal factors (economic activity, technical efficiency) and external factors for example Rencana Umum Energi Nasional (RUEN) General National Energy Plan regulatory pressure, national network losses of 8.2%, volatility in commodity prices) trigger this dynamic. The study's recommendations include: (1) mandatory integration of energy-saving technologies during production expansion, (2) an allocation of 20% annual capital expenditure for equipment upgrades, and (3) public-private collaboration in mitigating infrastructure challenges. These findings are the strategic foundation for achieving the national decarbonization target while mitigating the risk of operational inefficiencies.